Hematological profile and its correlation with reverse transcription–polymerase chain reaction-based serial quantitative detection of BCR-ABL in chronic myeloid leukemia patients at a referral cancer center - Vanita Pandey; Tamojit Chaudhuri; Amitabh Upadhyay; Somshankar Chowdhury; Sujata Mitra (Iraqi Journal of Hematology)
BACKGROUND: There are variations in the hematological profile among the Indian population affected with chronic myeloid leukemia (CML). The range of white blood cell count (WBC) was 0.46 × 109/mm3 to 1.86 × 109/mm3. Similarly, range for hemoglobin was 9–11 g/dl. WBC count can be as low as 0.18 × 109/mm3 even though CML is a myeloproliferative disorder. OBJECTIVE: The objective of this study was to correlate BCR-ABL expression with the hematological and myeloid proliferative parameters. METHODS: The present study was a single-center, hospital-based follow-up study among 66 cases of CML. The sample of patients was analyzed for BCR-ABL gene expression; hematological parameters and myeloid proliferative parameters such as band forms, myelocytes, metamyelocytes, and blast were also measured. Some patients reported twice, some thrice, and the total count after all follow-up for all 66 cases was 179. RESULTS: The mean age was 43.15 years. Men were more than women with male-to-female ratio of 1.6:1. The mean hemoglobin was lesser at 10.8 g/dl. Median total count was normal at 5610 (interquartile range = 2750) per μl. Mean neutrophils, lymphocytes, monocytes, basophils, and platelets were normal. The eosinophil count was raised. The BCR-ABL gene expression was positively and significantly correlated with total count. It was negatively and significantly correlated with lymphocytes and monocytes. It was not correlated with other hematological parameters. All the myeloid proliferative parameters, namely, band forms, myelocytes, metamyelocytes, and blast, were positively and significantly correlated with BCR-ABL gene expression. CONCLUSION: Total count and all myeloid proliferative parameters were positively and significantly correlated with BCR-ABL gene expression. Lymphocytes and monocytes were negatively correlated. These parameters can be used to track the disease progression in patients with CML.